(untitled) (Revista de Ciências Agroveterinárias, 2023)
The objective of this study was to quantify the main dendrometric variables, biomass and stored carbon of fragments of the Mixed Ombrophilous Forest of different successional levels, in different selected strata. The database used was obtained from the inventory carried out in the municipalities of Campo Belo do Sul and Capão Alto (SC), in fragments of Mixed Ombrophilous Forest classified as secondary (last interventions in 1960) and primary (preserved during the "wood cycle")), following the methodology of the Forest Floristic Inventory of Santa Catarina (IFFSC). The determination of volume and biomass were performed using equations in the literature, and carbon was determined by the methodology of the Intergovernmental Panel on Climate Change (IPCC). For the dendrometric characteristics, the study showed great variation between the successions and within the strata, which is expected in the case of a forest with a great variety of species, in which some differences may be indicative of past interventions. In all variables, Araucaria angustifolia has a large participation in the Primary Forest, being much smaller in the Secondary, and the same happens for the species Dicksonia sellowiana. From this study it is concluded that secondary forests differ from primary forests both in floristics and structure, and even in areas considered primary, such as the one in this study, it is seen that they do not reach the stock of advanced successional stages, possibly due to interventions prior to the known history of the area.